Exclusion of the familial Mediterranean fever locus as a susceptibility region for autosomal dominant familial Hibernian fever. Issue 5 (May 1998) - McDermott, M F; McDermott, E M; Quane, K A; Jones, L C; Ogunkolade, B W; Curtis, D; Waldron-Lynch, F; Phelan, M; Hitman, G A; Molloy, M G; Powell, R J
Abstract : Autosomal dominant periodic fevers constitute a range of syndromes characterised by recurrent attacks of fever and abdominal pain. Familial Hibernian fever (FHF) has been described in only one United Kingdom based family, but two other Irish families have been found with similar clinical features. FHF resembles familial Mediterranean fever (FMF) in several clinical features, but the mode of inheritance of FHF is dominant whereas FMF is recessive. We have investigated whether autosomal dominant periodic fevers, in particular FHF, map to the FMF susceptibility locus (MEFV) on chromosome 16p13.3. We have used informative microsatellite markers flanking this locus to genotype members of the three families mentioned above. Two point and multipoint lod scores definitively excluded linkage to MEFV in the two larger families. A haplotype study confirmed these findings, indicating that FHF is genotypically as well as phenotypically distinct from FMF.